Between Political Myths, Dormant Resentments, and Redefinition of the Recent History: A Case Study of Serbian National Identity - Wygnańska, Joanna (Qualitative Sociology Review, 2021)
The subject of the article concerns the issue of constructing and reconstructing national identity. The object of interest here is a sociological case study of Serbian national identity. It includes reconstruction and interpretation of in-depth interviews conducted in Serbia with the representatives of Serbian symbolic elites. The concept of symbolic elites is approached in the discussed research from Teun van Dijk’s perspective. Thus, they are individuals and groups directly involved in the production of public opinion, who have an impact on the content of publicly available knowledge, and the creation and legitimization of public discourse. The work is embedded in the methodological framework of Critical Discourse Analysis (CDA) and is based on the assumptions of the Discourse‐Historical Approach (DHA). In this optics, the most important thing is the historical and social context of the studied process of the discursive construction of national identity. Therefore, the conclusions also touch upon the historical, political, and social perspective of the formation of Serbian national identity. The reflection also aims at presenting the analysis from the contemporary perspective (mainly in 2008-2020). Thus, paying attention to the political divisions in Serbia and the country’s road to democratization and European integration, the discussed research study shows the comprehensive specifics of the studied national identity.